Các yếu tố tác động đến việc tham gia nghiên cứu khoa học của giảng viên dạy tiếng Anh tại Trường Đại học Cần Thơ - Ngô , Huỳnh Hồng Nga; Lê , Công Tuấn (Tạp chí Giáo dục, 2023)
It is very important and essential for lecturers to engage in research activities in order to develop their professional expertise. Nowadays, studies focusing on lecturers’ research in the field of English language teaching are still very limited and little is known about factors influencing research engagement of English as a foreign language (EFL) lecturers. Employing phenomenology as a research approach, this study explores EFL lecturers’ experiences related to the influential factors on their research engagement. The findings from this study show that personal commitment and motivation had significant effects on the lecturers’ research engagement. Drawing on the ecological systems theory, this study demonstrates that national, institutional and individual factors had both positive and negative impacts on the lecturers’ research engagement.